2018
DOI: 10.7717/peerj.4289
|View full text |Cite
|
Sign up to set email alerts
|

The importance of local settings: within-year variability in seawater temperature at South Bay, Western Antarctic Peninsula

Abstract: The Western Antarctic Peninsula (WAP) has undergone significant changes in air and seawater temperatures during the last 50 years. Although highly stenotherm Antarctic organisms are expected to be severely affected by the increase of seawater temperature, high-resolution datasets of seawater temperature within coastal areas of the WAP (where diverse marine communities have been reported) are not commonly available. Here we report on within-year (2016–2017) variation in seawater temperature at three sites on Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 58 publications
1
29
0
2
Order By: Relevance
“…Specific marine ecological and oceanographic conditions due to the close proximity of shifting hydrological fronts make the Kerguelen islands a unique observation site providing valuable baseline for assessing the effects of climate change on marine communities and ecosystem functioning. Significant effects are expected on local benthic communities, members of which have limited regulatory abilities (Stenni et al, 2017;Gutt et al, 2018;Cárdenas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Specific marine ecological and oceanographic conditions due to the close proximity of shifting hydrological fronts make the Kerguelen islands a unique observation site providing valuable baseline for assessing the effects of climate change on marine communities and ecosystem functioning. Significant effects are expected on local benthic communities, members of which have limited regulatory abilities (Stenni et al, 2017;Gutt et al, 2018;Cárdenas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the increase of shallow seawater temperature could result in a negative impact on various stenothermal species [ 4 ]. Sudden changes in sea surface temperature and salinity has been reported in Potter Cove (King George Island) [ 5 ] and also in some areas of the Antarctic Peninsula [ 6 ]. Recently, high mortality of krill has been reported near to Carlini Station related to significant increases of particulate matter of glacial origin produce by increased temperature [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreno et al 1977;Moreno & Osorio, 1980;Moreno, 1980;Zamorano, 1983;Zamorano et al 1986). A study related to climate change was initiated by Cárdenas (2016) who focused on the effect of global warming on Antarctic sponges in South Bay, and later on, Cárdenas et al (2018) reported within-year (2016-2017) variation in seawater temperature at three sites at South Bay, Doumer Island.…”
Section: Introductionmentioning
confidence: 99%